112k views
4 votes
What is the sum of the polynomials?

11x^2-5
+ x+4
_____

10x^-9
11x^2-x-9
11x^2+x-1
12x^2-1

Its C

User Allart
by
5.3k points

2 Answers

3 votes

Hi there!

Answer:


\boxed{11x^2 + x - 1}

Explanation:


11x^2-5+x+4


= 11x^2 - 5 + x + 4

Now combine the like terms.


= 11x^2 + -5 + x + 4


= (11x^2) + (x) + (-5 + 4)


= 11x^2 + x + -1

Have a great day!

User Tom Hallam
by
5.1k points
2 votes
11x^2 +x -1
You start with the greater power and add the like terms -5+4= -1
User Bushwacka
by
5.8k points